PENGARUH PERPUTARAN KAS, PERPUTARAN PIUTANG DAN PERPUTARAN MODAL KERJA TERHADAP RETURN ON ASSETS (ROA) PADA PERUSAHAAN SUB SEKTOR PROPERTY & REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014-2018 - Parlina, Nurhana Dhea; Haris, Abdul; Dheyyanto, Benny; Maylan, Siti Marwa (Transpublika Publisher, 2022)
The economic growth rate in 2018 has remained flat in the area of 5% because people's purchasing power has not increased significantly. In early April 2018, this highlighted the performance of four issuers that reported a reduction in profits, with some declines to 98% year on year (YoY). This study aims to determine the effect of Cash Turnover, Accounts Receivable Turnover, and Working Capital Turnover on Return on Assets simultaneously in property & real estate sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2014-2018 period. The type of research used is associative which aims to determine the relationship between two or more variables that are causal. Determination of the sample using purposive sampling method in order to obtain a sample of 9 companies with an observation period of 5 years. This data processing uses IBM SPSS Version 23. The data analysis technique uses multiple linear regression. The findings revealed that simultaneously the cash turnover variable, receivable turnover variable and working capital turnover variable had a significant and significant effect on return on assets.